Respuesta :
hypotenuse ^2= leg1 ^2+ leg2 ^2
25^2= 24^2 + leg2 ^2
leg2 ^2= 25^2-24^2= 625- 576=49
⇒ leg = V49
⇒ leg= 7
25^2= 24^2 + leg2 ^2
leg2 ^2= 25^2-24^2= 625- 576=49
⇒ leg = V49
⇒ leg= 7
Phytagoras' Theorem states that in any right triangle, the square of the hypotenuse is equal to the sum of the squares of the two legs. If c represents the hypotenuse, a and b represent the two leg, the theorem could be written as below.
c² = a² + b²
a² + b² = c
From the question, we could get information that
c = 25
a = 24
and we should find the value of b
Plug in the numbers to the formula
a² + b² = c²
24² + b² = 25²
576 + b² = 625
b² = 625 - 576
b² = 49
b = √49
b = 7
The length of the other leg is 7
c² = a² + b²
a² + b² = c
From the question, we could get information that
c = 25
a = 24
and we should find the value of b
Plug in the numbers to the formula
a² + b² = c²
24² + b² = 25²
576 + b² = 625
b² = 625 - 576
b² = 49
b = √49
b = 7
The length of the other leg is 7